PERANAN POLITIK HUKUM DALAM PEMBENTUKAN UNDANG-UNDANG NOMOR 18 TAHUN 2019 TENTANG PESANTREN - Nisan Rolan Wijaya; Tangkas Hadi Perwira; Rahman Syawal Rusman (Universitas Muhammadiyah Jember, 2020)
Political of Law covers the creation and implementation of the law to be built and enforced. Legal politics are found in the process of political decision making. Political decisions relating to basic principles, other policies and regulations include the field of religious education. Nevertheless, legal politics is a means used by the state to create a national legal system, where the legal system is expected to realizing the ideals of the nation that is contained in the Constitution of the year 1945 where One is to educate the life of the nation, including this is the legal politics of the establishment of law on Pesantren. The legal determination of the Pesantren has a strong philosophical, sociological and juridical policy that can be accounted for, it proves that the Pesantren has grown and developed in the community in an effort to improve Faith and Piety and Akhlakul Karimah with his trademark has been instrumental in realizing Islam to be a blessing for all nature, which proved to have a concrete role in the struggle to realize the independent Indonesia and participate in National development of the Republic of Indonesia.